RESPONS INTELEKTUAL MUSLIM TERHADAP TEORI EVOLUSI - Muhammad Hilal (AL-FIKRA, 2018)
This research aims to inquire the response of Muslim intellectuals toward the theory of evolution. It will trace how the theory of evolution is responded and received from the beginning of the coming of this evolutionary ideas into Muslim world to the recent times. After explaining the responses, this research will make a typology in which be drawn the types of each responses. This research uses qualitative method with the type of library research. From the exploration of those responses, this paper finds three types of responses. The first one is literal response which refuse the whole idea of evolution. The second is apologetic response which accept the idea of evolution, but refuse it in the human domain. The third is liberal response which accept the idea of evolution, either in animal or human domain, but reconsider the idea of “randomness” and “chance”.